Near-simultaneous intravital microscopy of glucose uptake and mitochondrial membrane potential, key endpoints that reflect major metabolic axes in cancer. Issue 1 (December 2017) - Zhu, Caigang; Martinez, Amy; Martin, Hannah; Li, Martin; Crouch, Brian; Carlson, David A.; Haystead, Timothy; Ramanujam, Nimmi
Abstract While the demand for metabolic imaging has increased in recent years, simultaneousin vivo measurement of multiple metabolic endpoints remains challenging. Here we report on a novel technique that providesin vivo high-resolution simultaneous imaging of glucose uptake and mitochondrial metabolism within a dynamic tissue microenvironment. Two indicators were leveraged; 2-[N-(7-nitrobenz-2-oxa-1, 3-diazol-4-yl) amino]-2-deoxy-D-glucose (2-NBDG) reports on glucose uptake and Tetramethylrhodamine ethyl ester (TMRE) reports on mitochondrial membrane potential. Although we demonstrated that there was neither optical nor chemical crosstalk between 2-NBDG and TMRE, TMRE uptake was significantly inhibited by simultaneous injection with 2-NBDGin vivo . A staggered delivery scheme of the two agents (TMRE injection was followed by 2-NBDG injection after a 10-minute delay) permitted near-simultaneousin vivo microscopy of 2-NBDG and TMRE at the same tissue site by mitigating the interference of 2-NBDG with normal glucose usage. The staggered delivery strategy was evaluated under both normoxic and hypoxic conditions in normal tissues as well as in a murine breast cancer model. The results were consistent with those expected for independent imaging of 2-NBDG and TMRE. This optical imaging technique allows for monitoring of key metabolic endpoints with the unique benefit of repeated, non-destructive imaging within an intact microenvironment.